2019
DOI: 10.1002/jsfa.9683
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency heating for powder pasteurization of barley grass: antioxidant substances, sensory quality, microbial load and energy consumption

Abstract: BACKGROUND: Young barley grass powder contains abundant nutrition and its antioxidant substances are severely impaired by radiation ( 60 Co) sterilization. To overcome product quality degradation, radiofrequency pasteurization was conducted using pilot-scale radiofrequency equipment (27 MHz, 6 kW) with electrode gaps of 12, 14 and 16 cm, while hot-air (80 ∘ C) pasteurization was used for comparison. RESULTS: Assessment suggested that uneven radiofrequency heating was improved for the 14 cm electrode gap. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…However, the fiber degradation in the barley grass destructed numerous fissures and porous structure, and the less fissures and porous structures result in low value of water‐holding capacity and oil‐holding capacity. Other studies found that apple dietary fiber after UMC also appeared a decline in dissolving capacity (Alsuhaibani, 2015; Cao et al., 2018b, 2019). The reason might be different physicochemical properties of barley grass and apple fiber.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the fiber degradation in the barley grass destructed numerous fissures and porous structure, and the less fissures and porous structures result in low value of water‐holding capacity and oil‐holding capacity. Other studies found that apple dietary fiber after UMC also appeared a decline in dissolving capacity (Alsuhaibani, 2015; Cao et al., 2018b, 2019). The reason might be different physicochemical properties of barley grass and apple fiber.…”
Section: Resultsmentioning
confidence: 90%
“…(2018) found that barley grass powder is rich in chlorophyll, protein, vitamins, minerals, and other nutrients. In particular, it is high in antioxidants, chlorophyll, flavonoids, and dietary fiber (Cao et al., 2017, 2019; Mujoriya & Bodla, 2011). Barley grass powder is helpful in controlling some diseases, such as diabetes and rheumatic disease (Rana et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition could be due to higher oxidation in MVD. Higher temperature causes mass oxidation and decomposition to form charring substances [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…MVD led to browning and increased bitterness, which lowered the evaluation scores. The main reason might be non-enzymatic oxidation resulting in darkness and bitterness [12,26]. This means that MVD leads to charring causing bitterness and forms sweet substances by high volume heat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation